Fabrication of lithium-ion batteries based on various LiNi1-xCoxO2 cathode materials. (23rd May 2019) - Pham, Thu Thi; Monajjemi, Majid; Dang, Chien Mau
Samples from the proposed LiNi1-x Cox O2 system were synthesised using the sol-gel method. Stoichiometric weights of LiNO3, Co(Ac)2 .2H2 O and Ni(COOCH3 )2 .4H2 O, have been considered for fabrication of Lix Niy Coz O2 . Five samples of LiNi1-x Cox O2 (x = 1, 0.8, 0.6, 0.5 and 0.3) of lithium, nickel and cobalt composition have been selected and synthesised. Charge-discharge characteristics of LiNi1-x Cox O2 (x = 1, 0.8, 0.6, 0.5 and 0.3) were investigated by performing cycle tests in the range of 2.0-4.5 V. Our results confirmed that, although these systems can help for removing the disadvantages of cobalt which are mainly is its cost and toxicity, the performance of these systems is similar to LiCoO2 cathode material.